2014
DOI: 10.5194/bg-11-5733-2014
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variations in the nitrogen cycle in the Arabian Sea

Abstract: Abstract. The Arabian Sea plays an important role in the marine nitrogen cycle because of its pronounced mid-water oxygen minimum zone (OMZ) in which bio-available nitrate (NO − 3 ) is reduced to dinitrogen gas (N 2 ). As the nitrogen cycle can respond fast to climate-induced changes in productivity and circulation, the Arabian Sea sediments are an important palaeoclimatic archive. In order to understand seasonal and interannual variations in the nitrogen cycle, nutrient data were obtained from the literature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 71 publications
(96 reference statements)
5
41
0
Order By: Relevance
“…However, the simulated OMZ in the Arabian Sea is too weak in this very coarse resolution model, raising concern about its reliability in the region. In the Holocene, large-scale ventilation changes may have played an important role together with the fluctuations in monsoon intensity as suggested by recent studies (Rixen et al, 2014;Gaye et al, submitted;Das et al, 2017). For instance, recent paleo-reconstructions by Das et al (2017) suggest an intensification of the Arabian Sea OMZ from the middle to late Holocene despite a weakening of the SWM winds.…”
Section: Implications For Paleo-studiesmentioning
confidence: 86%
“…However, the simulated OMZ in the Arabian Sea is too weak in this very coarse resolution model, raising concern about its reliability in the region. In the Holocene, large-scale ventilation changes may have played an important role together with the fluctuations in monsoon intensity as suggested by recent studies (Rixen et al, 2014;Gaye et al, submitted;Das et al, 2017). For instance, recent paleo-reconstructions by Das et al (2017) suggest an intensification of the Arabian Sea OMZ from the middle to late Holocene despite a weakening of the SWM winds.…”
Section: Implications For Paleo-studiesmentioning
confidence: 86%
“…Oxygen concentrations in its core and its volume vary in response to the seasonality of ventilation, probably related to the seasonality of isopycnal mixing (Banse et al, 2014;Rixen et al, 2014). Models produce similar patterns with major ventilation from the south during the SW monsoon, while reversing currents, progressive oxygen consumption, and isopycnal mixing reduce oxygen concentrations in the entire basin during the winter monsoon (Resplandy et al, 2012;Rixen et al, 2014).…”
Section: Study Areamentioning
confidence: 96%
“…Oxygen concentrations in its core and its volume vary in response to the seasonality of ventilation, probably related to the seasonality of isopycnal mixing (Banse et al, 2014;Rixen et al, 2014). Models produce similar patterns with major ventilation from the south during the SW monsoon, while reversing currents, progressive oxygen consumption, and isopycnal mixing reduce oxygen concentrations in the entire basin during the winter monsoon (Resplandy et al, 2012;Rixen et al, 2014). Reoxygenation during the SW monsoon occurs via the invigorated Somali Current in the western Arabian Sea and a northward-flowing undercurrent below 150 m of water depth along the SW coast of India (Resplandy et al, 2012), which was found up to 20 • N (Shetye et al, 1990).…”
Section: Study Areamentioning
confidence: 99%
“…The intensity of the OMZ and denitrification is seasonally variable. Oxygen concentrations in its core and its volume vary in response to the seasonality of ventilation, probably related to the seasonality of isopycnal mixing (Banse et al, 2014;Rixen et al, 2014). Models produce similar patterns with major ventilation from the south during the SW monsoon, while reversing currents, progressive oxygen consumption, and isopycnal mixing reduce oxygen concentrations in the entire basin during the winter monsoon (Resplandy et al, 2012;Rixen et al, 2014).…”
Section: Corementioning
confidence: 96%